Future lived experience: inclusive research with people living with dementia. (October 2020) - Williams, Val; Webb, Joe; Read, Sandy; James, Roy; Davis, Harry
People with a diagnosis of dementia have often been the subjects of qualitative research; by contrast, this article sets out to reflect on the positioning of people living with dementia in inclusive or 'co-produced' research and the connections between the personal and the collective voice in research. The article seeks to explore the unique hallmarks of inclusive dementia research, compared with some of the other models of inclusive research. Drawing on our experiences in one study, we describe the stages at which the research was set up, how a group of people living with dementia got involved in doing research, and their role in a conversation analysis of video interaction. We then use short extracts from recorded data of our meetings to discuss some of the tensions and challenges in this type of inclusive research, including political identification, the unequal power balance in inclusive research and the unique contributions of people living with dementia. Our ensuing argument is for a type of guided spontaneity, where lived experience (and future lived experience) has a space to be valued and to offer insights for research. The implications of inclusive research are about the practical, and about impact. These messages are contained in a postscript written by the last three authors Roy James, Sandy Read and Harry Davis, who are the members of the dementia research group.